STRATEGI PENGEMBANGAN SEKOLAH PERTANIAN ADIWIYATA AGRIBISNIS SMKN 1 PLOSOKLATEN KAB. KEDIRI - Mokhamad Atikhul Hidayat (Universitas Islam Kadiri, 2020)
Development in agriculture is directed to increase farmers' income and living standards. Expanding employment and business opportunities. Development of agriculture will not be separated from the education of skilled human resources tough and care about the environment because agricultural development will not be separated from the quality and availability of natural resources. In an effort to accelerate the development of Environmental Education in particular the formal education path at the level of primary and secondary education, to encourage the creation of knowledge and awareness of school residents in an effort to conserve the environment then on February 21, 2006 has been proclaimed ADIWIYATA. The Adiwiyata is one of the Ministry of Environment's programs. This program is a form of appreciation given by the government to the formal education institutions that are considered meritorious in developing environmental education. The objective of the Adiwiyata program is to realize the school's citizens who are responsible for the protection and management of the environment through good school governance. ADIWIYATA school-oriented school of agriculture is expected to improve the quality of agricultural human resources better so as to increase the economic value and income of farmers to improve the welfare of farmers. Therefore in need of thinking strategic step about the important role of the development of education ADIWIYATA agribusiness in national economic development hence the reason for the need of research on development strategy of ADIWIYAYA Agriculture school. Research carried out a survey based on the description method of analysis, which illustrates the problem according what is and is based on the fact that just took place (ex post facto). Analysis of the data used is qualitative data analysis method is by outlining the problems that exist with the sentences that aim to explain the problems taht occur so that will be a clear conclusion by using SWOT analysis. The result showed that the strategy of developing the first school of agribusiness strategy value (SO) which has the highest score of 4.28 this strategy can be taken from SWOT analysis by using internal strength to reach the opportunities that will emerge that is utilizing human resources and SDA to produce package Education that varies and enhances and expands the promotion.